185k views
1 vote
Solve the system by substitution.

y=x^2+4x+1
y=x+1

A. (1,2),(5,6)

B. (-1.0),(3/2,5,2)

C. (0,1),(-3,-2)

D. (3,4),(1,2)

2 Answers

3 votes

Answer:

C

Explanation:

We can substitue equation 2 into equation because y is common in both equations:

1. y=x^2+4x+1

2. y=x+1

therefore:


x+1=x^2+4\cdot{x}+1

We can take x+1 to the right side:


0=x^2+3\cdot{x}

We can write it as multiples of x:


0=x\cdot{(x+3)}

Therefore the answer is x=0 or x=-3 and therefore we can substitute into equation 1 and 2. therefore for equation 1 and 2 when x=0


y=1

and when x=-3


y=-2

The answer is (0,1) and (-3,-2) which is C

User Nick Kennedy
by
4.9k points
2 votes

Answer:

C.(0,1),(-3,-2)

Explanation:

(x+1)=x^2+4x+1

0=x^2+3x

(x+3)(x+0)

x=-3 x=0

when x=-3, y=(3)^2+4(-3)+1=-2

when x=0, y=0^2+0x+1=1

User Victor Jozwicki
by
5.2k points